What Grounded Theory Is…A Critically Reflective Conversation Among Scholars. (October 2015) - Walsh, Isabelle; Holton, Judith A.; Bailyn, Lotte; Fernandez, Walter; Levina, Natalia; Glaser, Barney
Grounded theory (GT) is taught in many doctoral schools across the world and exemplified in most methodological books and publications in top-tier journals as a qualitative research method. This limited view of GT does not allow full use of possible resources and restrains researchers' creativity and capabilities. Thus, it blocks some innovative possibilities and the emergence of valuable theories, which are badly needed. Therefore, understanding the full reach and scope of GT is becoming urgent, and we brought together a panel of established grounded theory scholars to help us in this endeavor through a reflective conversation.